Impact Assessment of Floating and Alternative Feeds (Wolffia globosa) for Fish Rearing Technologies in Tripura, India (Indian Journal of Extension Education, 2025)
The study assessed the social, economic, and environmental impacts of floating feed– and Wolffia-based fish rearing technologies disseminated by the College of Fisheries, CAU (Imphal), Lembucherra, Tripura. An after-only design was employed with 140 respondents: 100 floating feed adopters chosen through simple random sampling and 40 Wolffia adopters through complete enumeration. Impact indicators across social, economic, and environmental domains were developed using Specific, Measurable, Achievable, Relevant, and Time-bound (SMART) criteria, expert-validated, and analysed with the Wilcoxon Signed-Rank Test, paired t-tests, and Spearman’s correlation. Floating feed adoption improved production (+16.75 kg cycle–¹), net returns (+Rs. 6,644.26), and feed efficiency [Apparent feed conversion ratio (AFCR) –0.23], raising the Economic Impact Score from 32.93 to 40.23 (p = 0.000). Social participation, awareness, and income increased, while the Environmental Impact Score fell from 23.996 to 19.146, reflecting improved water quality. Wolffia adoption also enhanced production (+18.48 kg cycle–¹), returns (+Rs. 4,804.35), and AFCR (–0.25), contributing to livelihoods, nutrition, and climate-resilient aquaculture. Major constraints included high floating feed price, supplier dependence, flood induced losses, and weak extension support. Overall, both technologies boosted aquaculture productivity, profitability, and sustainability, highlighting the need for technical services, training, and institutional support.